Analysis of Modernist Architectural Projects with Visual Interference in Brazil - Rossi, Marco Antonio; Grandini Serrano, Eliane Patricia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
Modernism was a movement that began in the 1920s through the critical activities of Oswald de Andrade, Menotti del Picchia, Mário de Andrade and others who warned against the appreciation of national roots. Thus exposed their ideas of renovating groups of artists who begin to unite around a new aesthetic proposal. Modern architecture in Brazil had their origins in European avant-garde in the early twentieth century as well, represented by architect Antonio Moya. In 1923 arrives in São Paulo Warchavchik the architect, who always insisted on the character while "modern" and "Brazilian" in its architecture. Following years: architects assert themselves fully, influencing young architects. This research aims to analyze the projects executed by some architects who rewrote and reshaped the architecture in Brazil with modernism and artistic / visual interference paneled walls and details inside these buildings.